Microstructural Mechanical Texture Evaluation of Food Materials Using Nanoindentation as a Function of Drying Time (Case Study: Baking of Cookies) - Cisneros M., Karla C. (Zamorano: Escuela Agrícola Panamericana, 2024)
The baking process alters food product mechanical properties due to phase movement and the application of heat. This leads to the formation of solid wall and porous channel networks at a microscale which have an impact on the final product’s macroscale quality. In fact, microstructure cell wall strength is closely related to the micromechanical properties and texture within the range of 0.1-100 µm. Despite this, limited research has been conducted on the micromechanical properties of baked goods. The aim of this study was therefore to investigate the microscale behavior of the mechanical properties of cookies using nanoindentation during baking time. Based on the loading and unloading curves of the nanoindentation test, as well as the Oliver and Pharr equations, the micromechanical properties of hardness, stiffness, and Young’s modulus were calculated along with the determination of the samples’ moisture content. All properties increased during baking compared to the early stages of the process. The lowest values were found in the 10-minute sample for all micromechanical properties. Subsequently, there was an increase at 15 minutes that remained without significant differences for the rest of the baking process. Moisture content showed significant differences from 10 to 30 minutes, followed by stabilization until the 60 minutes, where there was a significant reduction. Considering the present trends, the potential relations of the micromechanical properties, moisture content and ingredients interactions were explored. This reveals that baking process is a dynamic system with continuous changes, driven by the intricate interplay among the diverse ingredients.